Exceptional longevity and potential determinants of successful ageing in a cohort of 39 Labrador retrievers: results of a prospective longitudinal study. Issue 1 (December 2015) - Adams, Vicki; Watson, Penny; Carmichael, Stuart; Gerry, Stephen; Penell, Johanna; Morgan, David
Abstract Background The aim of this study was to describe the longevity and causes of mortality in 39 (12 males, 27 females) pedigree adult neutered Labrador retrievers with a median age of 6.5 years at the start of the study and kept under similar housing and management conditions. Body condition score was maintained between two and four on a 5-point scale by varying food allowances quarterly. The impact of change in body weight (BW) and body composition on longevity was analysed using linear mixed models with random slopes and intercepts. Results On 31 July 2014, 10 years after study start, dogs were classified into three lifespan groups: 13 (33 %) Expected (≥9 to ≤12.9 years), 15 (39 %) Long (≥13 to ≤15.5 years) and 11 (28 %) Exceptional (≥15.6 years) with five still alive. Gender and age at neutering were not associated with longevity (P ≥ 0.06). BW increased similarly for all lifespan groups up to age 9, thereafter, from 9 to 13 years, Exceptional dogs gained and Long-lifespan dogs lost weight (P = 0.007). Dual-energy x-ray absorptiometer scans revealed that absolute fat mass increase was slower to age 13 for Long compared with Expected lifespan dogs (P = 0.003) whilst all groups lost a similar amount of absolute lean mass (P > 0.05). Percent fat increase and percent lean loss were slower, whilst the change in fat:lean was smaller, in both the Exceptional and Long lifespan compared with Expected dogs to age 13 (P ≤ 0.02). Total bone mineral density was significantly lower for Expected compared to Exceptional and Long lifespan dogs (P < 0.04). Conclusions This study shows that life-long maintenance of lean body mass and attenuated accumulation of body fat were key factors in achieving a longer lifespan. The results suggest that a combination of a high quality plane of nutrition with appropriate husbandry and healthcare are important in obtaining a greater than expected proportion of Labrador retrievers living well beyond that of the expected breed lifespan: 89.7 % (95 % CI 74.8–96.7 %) dogs were alive at 12 years of age and 28.2 % (95 % CI 15.6–45.1 %) reaching an exceptional lifespan of ≥15.6 years.